The Squirrel-Cage Induction Motor Model and Its Parameter Identification Via Steady and Dynamic Tests - Morfin, Onofre (2018)
One of the most important bases for designing robust closed-loop controllers applied to induction motor with high performance is establishing its mathematical model and state observers, as well as the parameter identification with high accuracy. In this paper, a step-by-step mathematical model of the squirrel-cage induction motor is described at αβ coordinate frame where the parameters are defined in detailed form; the rotor flux linkages and load torque are estimated via an asymptotic observer; the induction motor parameter identification is performed via a data acquisition board, applying dynamic and steady-state tests. Inductances of the induction motor model are calculated using the proposed relationships between the magnetically coupled circuit and equivalent circuit model. The mathematical model, state observers, and parameter identification procedure of squirrel-cage induction motor are validated via comparison of simulation signals with their corresponding real-time signals. This validation is made experimentally by a steady-state test, where load conditions are changed via a dynamometer which is belt coupled with the squirrel-cage induction motor